PENGARUH KEBIJAKAN DIVIDEN DAN FAKTOR LAINNYA TERHADAP VOLATILITAS HARGA SAHAM PERUSAHAAN PERTAMBANGAN - Surahmat; Fifi Swandari; Dian Masita Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
This research aims to analyze the Effects of dividend yield (X1), dividend payout ratio (X2), and other factors, such as size(X3), debt to asset ratio (X4), growth (X5), and earning volatility (X) toward Share Price Volatility. The population in this study was mining companies listed in Indonesian Stock Exchage in the 2010-2014 period. The sampling method used was purposive sampling. Samples were selected based on predetermined criteria and so 10 companies were obtained as the samples. The research data were secondary data obtained from Indonesian Capital Market Directory and Annual Report in the2010-2014 period. The research hypothesis testing used the technique of multiple linear regression with Statistical Package for Social Science software version 22. The result of the research concludes that dividend payout ratio (DPR), size, debt to asset ratio (DAR), and earning volatility have negative and signicant effects on share price volatility. Other two independent variables, Dividend Yield and Growth, have no significant effect on share price volatility.The companies can influence and control the volatility of share price through dividend policy with higher payment dividend payout ratio.